Safety and effectiveness of tranexamic acid in reduction of post-partum hemorrhage in patients undergoing caesarean section in tertiary care hospital of Southern India - L., Girish B.; S. G., Shraddha; L., Dwarakanath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Obstetric haemorrhage is a leading cause of premature maternal mortality, accounting for at least 100,000 deaths each year worldwide. Tranexamic acid has been shown to reduce uterine blood loss in non-surgical aspect. The aim of the study is to evaluate the safety and effectiveness of TXA in prevention of post-partum hemorrhage in patients undergoing caesarean delivery and to compare the secondary clinical outcomes. Methods: In this prospective observational cross-sectional study, 50 pregnant women undergoing CD were selected in random pattern and divided into control and study group of 25 patients each, in the department of obstetrics and gynaecology in Sri. Siddhartha medical college, Tumakuru from November 2019 to October 2021. The study group were given 1 g of TXA intravenously and the control group did not receive TXA. All the pregnant women received 20 units of oxytocin following delivery. Results: Mean of the total blood loss in the study group was 67 % less than the control group. Secondary clinical outcomes such as need for blood transfusion, other surgical measures to stop bleeding were comparatively less in study group compared to control groups. To note, no significant difference in duration of hospital stay was found between two groups. Conclusions: Our study suggests that, a safe dose of 1g IV tranexamic acid prior to caesarean section has an effective role in reducing blood loss and significantly improved blood loss–related secondary clinical outcomes with fewer side effects.